In vivo requirement of TGF-β/GDNF cooperativity in mouse development: focus on the neurotrophic hypothesis - Rahhal, Belal Mahmoud Mustafa; Heermann, Stephan; Krieglstein, Kerstin (International journal of developmental neuroscience, 2008)
Neurotrophic factors are well-recognized extracellular signaling molecules that regulate neuron development including neurite growth, survival and maturation of neuronal phenotypes in the central and peripheral nervous system. Previous studies have suggested that TGF-β plays a key role in the regulation of neuron survival and death and potentiates the neurotrophic activity of several neurotrophic factors, most strikingly of GDNF. To test the physiological relevance of this finding, TGF-β2/GDNF double mutant (d-ko) mice were generated. Double mutant mice die at birth like single mutants due to kidney agenesis (GDNF−/−) and congential cyanosis (TGF-β2−/−), respectively. To test for the in vivo relevance of TGF-β2/GDNF cooperativity to regulate neuron survival, mesencephalic dopaminergic neurons, lumbar motoneurons, as well as neurons of the lumbar dorsal root ganglion and the superior cervical ganglion were investigated. No loss of mesencephalic dopaminergic neurons was observed in double mutant mice at E18.5. A partial reduction in neuron numbers was observed in lumbar motoneurons, sensory and sympathetic neurons in GDNF single mutants, which was further reduced in TGF-β2/GDNF double mutant mice at E18.5. However, TGF-β2 single mutant mice showed no loss of neurons. These data point towards a cooperative role of TGF-β2 and GDNF with regard to promotion of survival within the peripheral motor and sensory systems investigated.